2017
DOI: 10.24820/ark.5550190.p010.142
|View full text |Cite
|
Sign up to set email alerts
|

Effective synthesis of novel furan-fused pentacyclic triterpenoids via anionic 5-exo dig cyclization of 2-alkynyl-3-oxotriterpene acids

Abstract: An efficient synthetic route to biologically interesting furan-fused pentacyclic triterpenoids with a furan moiety 2,3-annelated to the terpenoid skeleton has been developed. New heterocyclic triterpenoids have been obtained in moderate to good yields by base-promoted 5-exo-dig cyclization of the pent-4-yn-1-one moiety in ring А of the 2-alkynyl-3-oxotriterpene acids of lupane, ursane and oleane type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…[26] Notably, this base-promoted cyclization of 4-pentynones was also introduced to the synthesis of furan-fused pentacyclic triterpenoids by Spivak's group, starting from 2-alkynyl-3-oxotriterpene acids. [33] In 2014, we developed an efficient and straightforward DBU-promoted intramolecular regioselective cyclization of 4acetylenic ketones 68 to afford stereodefined 2-methylene-2,3dihydrofurans 69 (Scheme 13). Diverse of 4-acetylenic ketones with varied functional groups proceeded smoothly in good to excellent yields.…”
Section: Base-promoted Cyclizations Of 4-acetylenic Ketonesmentioning
confidence: 99%
“…[26] Notably, this base-promoted cyclization of 4-pentynones was also introduced to the synthesis of furan-fused pentacyclic triterpenoids by Spivak's group, starting from 2-alkynyl-3-oxotriterpene acids. [33] In 2014, we developed an efficient and straightforward DBU-promoted intramolecular regioselective cyclization of 4acetylenic ketones 68 to afford stereodefined 2-methylene-2,3dihydrofurans 69 (Scheme 13). Diverse of 4-acetylenic ketones with varied functional groups proceeded smoothly in good to excellent yields.…”
Section: Base-promoted Cyclizations Of 4-acetylenic Ketonesmentioning
confidence: 99%
“…Gubaidullin et al prepared C (2)-alkynyl derivatives of BoA, presenting several aryl and heterocyclic substituents [74,75] and starting from C (2)-propargyl derivative 93a with an equatorial-oriented α-propynyl group (Scheme 17). The products 115a – o were obtained in fair to very good yields (43%–89%) by Sonogashira reactions in the presence of bis(triphenylphosphane)palladium(II) dichloride, copper(I) iodide, and triethylamine (Scheme 25).…”
Section: Palladium-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
“…Also, Gubaidullin et al reported the gold-catalyzed intramolecular heterocyclization of compounds 115a – n [74,75], whose synthesis was described previously in Scheme 25. It occurred in the presence of 2 mol% PPh 3 AuCl and 2 mol% AgOTf in toluene at room temperature and afforded methyl [3,2- b ]furan-based betulonate derivatives 138a – n in high yields (36%–92%) over a short period of time (Scheme 33).…”
Section: Synthesis Of Heterocycle-fused Ba/hba Derivativesmentioning
confidence: 99%
“…Previously, we used this feature of the C‐2 position for introducing the propynyl substituent into triterpene acid molecules via α‐alkylation of the potassium enoxytriethylborates, generated on treatment with the KN(SiMe 3 ) 2 – Et 3 B reagents in ether type solvents, with propargyl bromide (Scheme ). The C‐2 propargyl derivatives betulonic, ursonic, and oleanonic acids were successfully involved into metal‐catalyzed 1,3‐dipoar cycloaddition to sugar azides and intramolecular 5‐ exo ‐ dig ‐cyclization ,. In this communication, we report the use of propargyl‐containing triterpenoids 2–9 for the synthesis of symmetrical and unsymmetrical triterpene 1,3‐diynes by copper‐ and palladium‐catalyzed acetylenic homocoupling and cross‐coupling.…”
Section: Introductionmentioning
confidence: 98%